2018
DOI: 10.3399/bjgp18x696233
|View full text |Cite
|
Sign up to set email alerts
|

GPs’ understanding and practice of safety netting for potential cancer presentations: a qualitative study in primary care

Abstract: GPs would benefit from clearer guidance on which aspects of clinical practice contribute to effective safety netting for cancer. Practice systems that enable active follow-up of patients with low-risk-but-not-no-risk symptoms, which could represent malignancy, could reduce delays in cancer diagnosis without increasing GP workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 21 publications
2
46
0
1
Order By: Relevance
“…6,26,27 Varied notions of paternalism, largely as a result of workload pressures, have also been reported in a qualitative study of GPs' practice of 'safety netting' for potential cancer presentations. 19 The range of explanations for nonattendance and their potential to increase the diagnostic interval were consistent with elements of the Andersen model of total patient delay. 11 The importance of system flaws is magnified by time pressures within an urgent referral process with performance targets.…”
Section: Comparison With Existing Literaturesupporting
confidence: 68%
See 1 more Smart Citation
“…6,26,27 Varied notions of paternalism, largely as a result of workload pressures, have also been reported in a qualitative study of GPs' practice of 'safety netting' for potential cancer presentations. 19 The range of explanations for nonattendance and their potential to increase the diagnostic interval were consistent with elements of the Andersen model of total patient delay. 11 The importance of system flaws is magnified by time pressures within an urgent referral process with performance targets.…”
Section: Comparison With Existing Literaturesupporting
confidence: 68%
“…Most GPs described follow-up whereby practice receptionists telephoned nonattending patients and at times GPs made these calls themselves; partly to enable medical discussion and to reflect the greater respect patients were felt to have for GPs. This could be seen as an example of 'safety netting', 19 though none of the GP participants used that term. Meanwhile, some GPs felt that the onus should be on the patient to attend and an informed decision not to attend should be respected: 'If they don't take you up on that offer and they've already been offered an appointment for a test and they've declined that, then I think at some point you might need to respect the patient's autonomy.'…”
Section: Negotiating Responsibilitymentioning
confidence: 99%
“…Consensus safety netting guidance aims to ameliorate this by stating that GPs should give specific information about when and how best to re-consult, including who has the responsibility to make the appointment 3. Our own work has shown that GPs report relying on competent patients to take the responsibility to act on that advice to re-consult once they have explained their thinking and expectations, while being more proactive in arranging follow-up for patients they perceive to be at higher risk or less able to take responsibility 25. Building on these findings, the aim of this paper is to explore patients’ and GPs’ accounts of how responsibility was perceived and shared in their own recent experiences of cancer safety netting.…”
Section: Introductionmentioning
confidence: 96%
“…These patients require appropriate and robust safety netting but, as pressures of time and workload increase in primary care, GPs report selecting patients perceived to be at higher risk for closer follow-up. 18 When safety netting patients with non-specific symptoms we should be mindful to discuss the implications of our chosen testing strategy including, as Just and colleagues 1 point out, the potential for overdiagnosis.…”
Section: Getting the Balance Rightmentioning
confidence: 99%